Porous hollow carbon sphere composite material, preparation method thereof and sodium ion battery

By using mesoporous hollow nanocarbon ball materials co-doped with nitrogen, phosphorus and sulfur in sodium ion batteries, the shortcomings of traditional carbon materials in cycling stability, discharge capacity and rate performance are solved, and more efficient battery performance is achieved.

CN119674062APending Publication Date: 2025-03-21BEIJING CHJ AUTOMOTIVE TECH CO LTD +1
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202311229624.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-21
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Traditional carbon materials have poor cycle stability in sodium ion batteries and cannot effectively suppress the shuttle effect, resulting in poor discharge capacity and rate performance.

Method used

Mesoporous hollow nanocarbon spheres co-doped with nitrogen, phosphorus and sulfur are used as the negative electrode active material. The hollow structure and mesoporous structure provide space to accommodate volume expanded particles, and the carbon layer spacing is expanded through the triple doping of nitrogen, phosphorus and sulfur to increase the active site.

Benefits of technology

It significantly improves the discharge capacity, rate performance and cycle stability of sodium ion batteries, and solves the shortcomings of traditional carbon materials in these aspects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119674062A_ABST
    Figure CN119674062A_ABST
Patent Text Reader

Abstract

The invention provides a porous hollow carbon sphere composite material, a preparation method thereof and a sodium ion battery, and belongs to the technical field of sodium ion batteries. The composite material is mesoporous hollow carbon nanospheres co-doped with nitrogen element, phosphorus element and sulfur element. According to the composite material, mesoporous hollow nano carbon spheres capable of providing negative electrode capacity are designed, and a hollow nano structure is used for providing a space for electrode volume expansion after circulation, so that the discharge capacity and the circulation stability in a sodium ion battery are improved; meanwhile, due to the mesoporous structure on the surface of the mesoporous hollow carbon nanosphere, the diffusion path of sodium ions is greatly shortened, and the separation and embedding of the sodium ions are promoted, so that the specific capacity of the negative electrode material is improved; in addition, by utilizing the synergistic effect of nitrogen, phosphorus and sulfur co-doping, the carbon layer spacing of the mesoporous hollow carbon nanospheres can be obviously enlarged, the active sites can be increased, and the rate capability and the cycling stability can be optimized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sodium ion batteries, and in particular relates to a porous hollow carbon ball composite material and a preparation method thereof, and a sodium ion battery. Background Art

[0002] The negative active materials of sodium ion batteries mainly include carbon materials, alloy materials, metal compounds, etc. Among them, carbon materials have the highest technical maturity and abundant resources, and are expected to be the first to achieve industrialization. Traditional carbon materials such as graphite, soft carbon and hard carbon cannot provide enough space for the volume change of electrode materials, and their low polarity makes them only provide weak physical adsorption, which cannot effectively inhibit the shuttle effect, resulting in poor cycle stability of the battery. Summary of the invention

[0003] The present invention aims to solve one of the technical problems in the related art at least to a certain extent. To this end, the embodiments of the present invention provide a porous hollow carbon sphere composite material and a preparation method thereof and a sodium ion battery.

[0004] The porous hollow carbon sphere composite material of the embodiment of the present invention is a mesoporous hollow nano-carbon sphere co-doped with nitrogen, phosphorus and sulfur.

[0005] The advantages and technical effects brought by the porous hollow carbon sphere composite material of the embodiment of the present invention are:

[0006] 1. The composite material of the embodiment of the present invention is designed with mesoporous hollow nano-carbon spheres that can provide negative electrode capacity, and the hollow structure is used to provide space for the volume expansion of particles after cycling, so as to improve the discharge capacity and cycle stability in the sodium ion battery;

[0007] 2. The composite material of the embodiment of the present invention has a nanostructure, which improves the transmission rate of electrons and sodium ions, provides space for the volume expansion of the electrode after cycling, and can ensure high discharge capacity, high rate performance and cycle stability;

[0008] 3. The composite material of the embodiment of the present invention has a mesoporous structure, rich pore structure, and a large specific surface area, which shortens the diffusion path of sodium ions and promotes the extraction and embedding of sodium ions, thereby improving the specific capacity of the negative electrode material;

[0009] 4. The composite material of the embodiment of the present invention is doped with nitrogen, phosphorus and sulfur at the same time. The synergistic effect brought about by the triple doping of nitrogen, phosphorus and sulfur can expand the carbon layer spacing, increase the surface functional groups and defects of the carbon material, provide more active sites, and achieve the improvement of rate performance and reversible capacity. If a single heteroatom or any two heteroatoms are doped, the above effects cannot be achieved.

[0010] In some embodiments, the diameter of the mesoporous hollow nano-carbon sphere is 70-100 nm; and / or the wall thickness of the mesoporous hollow nano-carbon sphere is 8-12 nm; and / or the surface of the mesoporous hollow nano-carbon sphere has mesopores with a pore size of 20-30 nm.

[0011] In some embodiments, based on 100% of the total atoms of the porous hollow carbon ball composite material, the atomic percentage content of the nitrogen element is 7-9%; and / or the atomic percentage content of the phosphorus element is 5-7%; and / or the atomic percentage content of the sulfur element is 2-4%.

[0012] In addition, an embodiment of the present invention further provides a method for preparing a porous hollow carbon sphere composite material, comprising the following steps:

[0013] (1) mixing dopamine hydrochloride, nano-calcium carbonate, a buffer and a solvent, separating and drying the reaction product after the reaction, and obtaining polydopamine-coated nano-calcium carbonate;

[0014] (2) subjecting the polydopamine-coated nano-calcium carbonate to a first calcination treatment in a protective gas atmosphere to obtain nitrogen self-doped carbon-coated nano-calcium carbonate;

[0015] (3) etching the nitrogen self-doped carbon-coated nano-calcium carbonate with an acidic etching solution, and then separating and drying the reaction product to obtain nitrogen self-doped mesoporous hollow nano-carbon spheres;

[0016] (4) subjecting the nitrogen self-doped mesoporous hollow nano-carbon spheres and the phosphorus-containing compound to a second calcination treatment in a mixed atmosphere of a sulfur-containing gas and a protective gas to obtain the porous hollow carbon sphere composite material.

[0017] The advantages and technical effects of the method for preparing the porous hollow carbon sphere composite material according to the embodiment of the present invention are as follows:

[0018] 1. In step (1), dopamine hydrochloride is used as a precursor, nano-calcium carbonate is used as a self-sacrificial template, and a buffer is used to provide a good chemical environment for the self-polymerization reaction of dopamine hydrochloride, and dopamine hydrochloride is polymerized on the outer surface of the nano-calcium carbonate to form a polydopamine shell;

[0019] 2. In step (2), polydopamine is used as a carbon source and a nitrogen source, and subjected to a first calcination treatment, so that the polydopamine is carbonized to form a nitrogen self-doped carbon coating layer on the surface of the nano-calcium carbonate;

[0020] 3. Step (3) removing the nano-calcium carbonate core in the nitrogen self-doped carbon-coated nano-calcium carbonate by reaction between an acidic etching solution and nano-calcium carbonate, leaving the nitrogen self-doped carbon coating layer, and using the carbon dioxide gas generated in the reaction process as a pore-forming agent, leaving holes in the nitrogen self-doped carbon coating layer during gas escape, thereby obtaining nitrogen self-doped mesoporous hollow nano-carbon spheres;

[0021] 4. In step (4), the nitrogen self-doped mesoporous hollow nano-carbon spheres are phosphated with a phosphorus-containing compound, and the nitrogen self-doped mesoporous hollow nano-carbon spheres are simultaneously sulfurized with a sulfur-containing gas to obtain nitrogen-phosphorus-sulfur self-doped mesoporous hollow nano-carbon spheres, i.e., porous hollow carbon sphere composite materials;

[0022] 5. Performing the first calcination treatment of step (2) before the etching treatment of step (3) can prevent the nitrogen self-doped mesoporous hollow nano-carbon spheres from collapsing, thereby ensuring that a porous hollow carbon sphere composite material with good performance can be finally formed;

[0023] 6. In step (4), phosphating and sulfiding are carried out simultaneously, which simplifies the preparation process and reduces the cost compared to carrying them out separately.

[0024] In some embodiments, in step (1), the mass ratio of the dopamine hydrochloride to the nano-calcium carbonate is (3-5):5; and / or, the reaction is carried out at room temperature under stirring for 24-48 hours.

[0025] In some embodiments, in step (2), the first calcination treatment is calcination at 400-900° C. for 4-12 hours.

[0026] In some embodiments, in step (2), the first calcination treatment is first calcined at 400-500° C. for 2-5 h and then calcined at 700-900° C. for 2-5 h.

[0027] In some embodiments, in step (3), the acidic etching solution is selected from at least one of hydrochloric acid, acetic acid, sulfuric acid, nitric acid and phosphoric acid.

[0028] In some embodiments, in step (3), the concentration of the acidic etching solution is 0.2-1.5 mol·L -1 .

[0029] In some embodiments, in step (4), the phosphorus-containing compound includes at least one of sodium hypophosphite, ammonium hypophosphite and red phosphorus; and / or the sulfur-containing gas includes at least one of hydrogen sulfide, sulfur dioxide and sulfur trioxide.

[0030] In some embodiments, in step (4), the second calcination treatment is calcination at 500-900° C. for 1-5 hours.

[0031] In addition, an embodiment of the present invention further provides a sodium ion battery, the negative electrode active material of the sodium ion battery includes the porous hollow carbon sphere composite material of the embodiment of the present invention or the porous hollow carbon sphere composite material prepared by the preparation method of the embodiment of the present invention.

[0032] The advantages and technical effects brought by the sodium ion battery of the embodiment of the present invention are as follows:

[0033] Due to the use of the porous hollow carbon sphere composite material of the embodiment of the present invention, or the porous hollow carbon sphere composite material prepared by the preparation method of the embodiment of the present invention, the sodium ion battery of the embodiment of the present invention has excellent discharge capacity, rate performance and cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 For sodium ion batteries at 0.5A·g -1 The charge and discharge curves of the first five cycles under the current density; wherein (a) is the sodium ion battery of Example 1; (b) is the sodium ion battery of Comparative Example 2; (c) is the sodium ion battery of Comparative Example 1;

[0035] Figure 2 1 is a discharge performance curve of a sodium ion battery at different rates; the curves from top to bottom are the sodium ion battery of Example 1, the sodium ion battery of Comparative Example 2, and the sodium ion battery of Comparative Example 1;

[0036] Figure 3 It is a Raman spectrum diagram; the curves from top to bottom are the nitrogen, phosphorus and sulfur co-doped mesoporous hollow nanocarbon spheres of Example 1, the nitrogen self-doped mesoporous hollow nanocarbon spheres of Comparative Example 2, and the solid nanocarbon spheres of Comparative Example 1.

[0037] Figure 4 It is a SEM image, and the area indicated by the dotted circle in the figure is the mesopore; among them, (a, d) are solid nano-carbon spheres of comparative example 1; (b, e) are nitrogen self-doped mesoporous hollow carbon spheres of comparative example 2; (c, f) are nitrogen, phosphorus and sulfur co-doped mesoporous hollow nano-carbon spheres of Example 1. DETAILED DESCRIPTION

[0038] Embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.

[0039] The embodiment of the present invention provides a porous hollow carbon sphere composite material, wherein the composite material is mesoporous hollow nano-carbon spheres co-doped with nitrogen, phosphorus and sulfur.

[0040] The composite material of the embodiment of the present invention is designed with mesoporous hollow nano carbon balls that can provide negative electrode capacity, and the hollow nano structure is used to provide space for the electrode volume expansion after the cycle, so as to improve the discharge capacity and cycle stability in the sodium ion battery; at the same time, the mesoporous structure on the surface of the mesoporous hollow nano carbon balls greatly shortens the diffusion path of sodium ions, promotes the extraction and embedding of sodium ions, thereby improving the specific capacity of the negative electrode material; in addition, by utilizing the synergistic effect of nitrogen, phosphorus and sulfur co-doping, the carbon layer spacing of the mesoporous hollow nano carbon balls can be significantly expanded, the active sites can be increased, the rate performance and cycle stability can be optimized, and the shortcomings of traditional carbon materials in terms of small carbon layer spacing, low reaction activity, low electron ion transmission efficiency, and few functional group sites can be improved. If it is a single heteroatom or any two heteroatoms doping, the above effects cannot be achieved.

[0041] In some embodiments, the diameter of the mesoporous hollow nano-carbon sphere is 70-100 nm, such as 70 nm, 75 nm, 80 nm, 85 nm, 90 nm, 95 nm, 100 nm, etc. When the diameter of the mesoporous hollow nano-carbon sphere is too small, it will be unfavorable for the insertion and extraction of sodium ions. When the diameter of the mesoporous hollow nano-carbon sphere is too large, the specific surface area is reduced, and the active sites are reduced.

[0042] In some embodiments, the wall thickness of the mesoporous hollow nano-carbon sphere is 8-12 nm, such as 8 nm, 8.5 nm, 9 nm, 9.5 nm, 10 nm, 10.5 nm, 11 nm, 11.5 nm, 12 nm, etc. When the wall thickness of the mesoporous hollow nano-carbon sphere is too small, it will be disadvantageous to improve the stability of the mesoporous hollow nano-carbon sphere; when the wall thickness of the mesoporous hollow nano-carbon sphere is too large, it will be disadvantageous for sodium ion transmission.

[0043] In some embodiments, the surface of the mesoporous hollow nano-carbon sphere has mesopores with a pore size of 20-30 nm, such as 20 nm, 21 nm, 22 nm, 23 nm, 24 nm, 25 nm, 26 nm, 27 nm, 28 nm, 29 nm, 30 nm, etc. When the pore size is too small, it is not conducive to the escape and embedding of sodium ions, thereby not conducive to improving the battery capacity; when the pore size is too large, it is not conducive to improving the structural stability of the mesoporous hollow nano-carbon sphere.

[0044] In some embodiments, based on the total number of atoms of the porous hollow carbon ball composite material as 100%, the atomic percentage content of the nitrogen element is 7-9%, for example, 7%, 7.2%, 7.4%, 7.6%, 7.8%, 8%, 8.2%, 8.4%, 8.6%, 8.8%, 9%, etc.; and / or the atomic percentage content of the phosphorus element is 1-3%, for example, 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.6%, 2.8%, 3%, etc.; and / or the atomic percentage content of the sulfur element is 2-4%, for example, 2%, 2.2%, 2.4%, 2.6%, 2.8%, 3%, 3.2%, 3.4%, 3.6%, 3.8%, 4%, etc. The heteroatoms within the above doping amount range can play a better synergistic effect, which can significantly expand the carbon layer spacing of the mesoporous hollow nanocarbon spheres, increase the active sites, and further optimize the rate performance and cycle stability. When the heteroatom doping amount is lower than the above mass fraction range, it will be unfavorable to improve the battery capacity; when the heteroatom doping amount is higher than the above mass fraction range, it will be unfavorable to improve the structural stability of the material.

[0045] In addition, an embodiment of the present invention further provides a method for preparing a porous hollow carbon sphere composite material, comprising the following steps:

[0046] (1) mixing dopamine hydrochloride, nano-calcium carbonate, a buffer and a solvent, separating and drying the reaction product after the reaction, and obtaining polydopamine-coated nano-calcium carbonate;

[0047] (2) subjecting the polydopamine-coated nano-calcium carbonate to a first calcination treatment in a protective gas to obtain nitrogen self-doped carbon-coated nano-calcium carbonate;

[0048] (3) etching the nitrogen self-doped carbon-coated nano-calcium carbonate with an acidic etching solution, and then separating and drying the reaction product to obtain nitrogen self-doped mesoporous hollow nano-carbon spheres;

[0049] (4) subjecting the nitrogen self-doped mesoporous hollow nano-carbon spheres and the phosphorus-containing compound to a second calcination treatment in a mixed atmosphere of a sulfur-containing gas and a protective gas to obtain the porous hollow carbon sphere composite material.

[0050] The preparation method of the embodiment of the present invention, in step (1), dopamine hydrochloride is used as a precursor, nano-calcium carbonate is used as a self-sacrificial template, and a buffer is used to provide a good chemical environment for the self-polymerization reaction of dopamine hydrochloride, and dopamine hydrochloride is polymerized on the outer surface of the nano-calcium carbonate to form a polydopamine shell. In step (2), polydopamine is used as a carbon source and a nitrogen source, and after a first calcination treatment, polydopamine is carbonized to form a nitrogen self-doped carbon coating layer on the surface of the nano-calcium carbonate. In step (3), the nano-calcium carbonate core in the nitrogen self-doped carbon-coated nano-calcium carbonate is removed by the reaction of an acidic etching solution with the nano-calcium carbonate, leaving the nitrogen self-doped carbon coating layer, and the carbon dioxide gas generated during the reaction is used as a pore-forming agent, and holes are left in the nitrogen self-doped carbon coating layer during the gas escape process, so that nitrogen self-doped mesoporous hollow nano-carbon spheres can be obtained. In step (4), the nitrogen self-doped mesoporous hollow nano-carbon spheres are phosphated with a phosphorus-containing compound, and the nitrogen self-doped mesoporous hollow nano-carbon spheres are sulfurized with a sulfur-containing gas to obtain nitrogen-phosphorus-sulfur self-doped mesoporous hollow nano-carbon spheres, that is, porous hollow carbon sphere composite materials.

[0051] In addition, the first calcination treatment of step (2) is performed before the etching treatment of step (3), which can prevent the nitrogen self-doped mesoporous hollow nano-carbon spheres from collapsing, thereby ensuring that a porous hollow carbon sphere composite material with good performance can be finally formed. If the polydopamine shell is firstly obtained by etching and then the polydopamine is carbonized to form the nitrogen self-doped mesoporous hollow nano-carbon spheres by the first calcination treatment, the collapse of the nitrogen self-doped mesoporous hollow nano-carbon spheres may be caused due to the lack of template during the first calcination treatment, which is not conducive to the final formation of the target product porous hollow carbon sphere composite material. In addition, in step (4), phosphating and sulfurizing are carried out simultaneously, which is simple in preparation process and low in cost compared to carrying out them separately.

[0052] In some embodiments, in step (1), the purity of dopamine hydrochloride is above 93%, for example 93%, 94%, 95%, 96%, 97%, 98%, 99%, 99.5%, 99.9%, etc., preferably the purity is above 99%.

[0053] In some embodiments, in step (1), the diameter of the nano-calcium carbonate is 60-90 nm, for example, 60 nm, 65 nm, 70 nm, 75 nm, 80 nm, 85 nm, 90 nm, etc.

[0054] In some embodiments, in step (1), the buffer is selected from at least one of phosphoric acid, citric acid, carbonic acid, acetic acid, barbituric acid and tris(hydroxymethyl)aminomethane (Tris). Preferably, the buffer is tris(hydroxymethyl)aminomethane (Tris), and its effective buffer range is pH=7.0-9.2, which is conducive to the self-polymerization reaction of dopamine hydrochloride in a stable buffer system and improves the reaction efficiency.

[0055] In some embodiments, in step (1), the mass ratio of the dopamine hydrochloride to the nano-calcium carbonate is (3-5):5, such as 3:5, 3.5:5, 4:5, 4.5:5, 5:5, etc. Dopamine hydrochloride undergoes self-polymerization on the surface of the nano-calcium carbonate microspheres to form a polydopamine shell, so the mass ratio of the two will affect the thickness of the polydopamine shell, and ultimately affect the wall thickness of the target product, the porous hollow carbon sphere composite material. When the mass ratio of dopamine hydrochloride to nano-calcium carbonate is too low, the wall thickness of the porous hollow carbon sphere composite material is too small. When the mass ratio of dopamine hydrochloride to nano-calcium carbonate is too high, the wall thickness of the porous hollow carbon sphere composite material is too large.

[0056] In some embodiments, in step (1), the reaction is carried out at room temperature under stirring for 24-48 hours, such as 24 hours, 28 hours, 32 hours, 36 hours, 40 hours, 44 hours, 48 ​​hours, etc. Dopamine hydrochloride self-polymerizes to form polydopamine, which facilitates the uniform coating of polydopamine on the surface of nano-calcium carbonate microspheres under stirring conditions, thereby improving the uniformity of the wall thickness of the target product porous hollow carbon sphere composite material. In addition, room temperature, such as 20°C, 21°C, 22°C, 23°C, 24°C, 25°C, etc., is a more suitable temperature condition for dopamine hydrochloride self-polymerization, and can reduce energy waste. In addition, the reaction time will affect the thickness of the polydopamine shell, and ultimately affect the wall thickness of the target product, the porous hollow carbon sphere composite material. By adjusting the reaction time to 24-48h, for example, 24h, 30h, 35h, 40h, 45h, 48h, etc., the thickness of the polydopamine shell can be adjusted, thereby optimizing the wall thickness of the target product, the porous hollow carbon sphere composite material; preferably, the reaction time is 30-40h.

[0057] In some embodiments, in step (1), the separation is carried out by centrifugation, so as to quickly separate the polydopamine-coated nano-calcium carbonate. There is no particular limitation on the drying method, drying temperature and drying time, as long as the water in the polydopamine-coated nano-calcium carbonate can be removed, so as to facilitate the subsequent first calcination treatment. Preferably, vacuum drying is carried out at a temperature of 40-100°C, such as 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, etc., for 8-24h, such as 8h, 10h, 12h, 14h, 16h, 18h, 20h, 22h, 24h, etc.

[0058] In some embodiments, in step (2), the first calcination treatment is calcined at 400-900°C, such as 400°C, 500°C, 600°C, 700°C, 800°C, 900°C, etc., for 4-12h, such as 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, etc. The calcination temperature and time are controlled within the above range, which can promote the complete carbonization of the polydopamine shell in the polydopamine-coated nano-calcium carbonate into a nitrogen self-doped carbon coating layer to obtain a nitrogen self-doped carbon-coated nano-calcium carbonate. Preferably, the first calcination treatment is calcined at 400-500°C for 2-5h and then at 700-900°C for 2-5h. The calcination is first calcined at a relatively low temperature and then at a relatively high temperature, which is conducive to uniform doping of heteroatoms and can improve the safety of experimental operation, because if the temperature rises too quickly, the calcining furnace will be damaged.

[0059] In some embodiments, in step (2), the protective gas is selected from argon and / or nitrogen. In the protective gas mentioned above, impurities can be avoided during the carbonization process of the polydopamine shell.

[0060] In some embodiments, in step (3), the acidic etching solution is selected from at least one of hydrochloric acid, acetic acid, sulfuric acid, nitric acid and phosphoric acid. The acidic etching solution of the above type reacts strongly with the nano-calcium carbonate core in the nitrogen self-doped carbon-coated nano-calcium carbonate, and can quickly remove the nano-calcium carbonate core to obtain nitrogen self-doped mesoporous hollow nano-carbon spheres. Preferably, the acidic etching solution is hydrochloric acid.

[0061] In some embodiments, in step (3), the concentration of the acidic etching solution is 0.2-1.5 mol·L -1 , for example 0.2 mol·L -1 , 0.4 mol·L -1 , 0.6mol·L -1 , 0.8 mol·L -1 , 1mol·L -1 , 1.2 mol·L -1 , 1.4 mol·L -1 , 1.5 mol·L -1 When the concentration of the acidic etching solution is too low, the reaction rate between the acidic etching solution and the nano calcium carbonate core is too slow, which is not conducive to improving production efficiency. When the concentration of the acidic etching solution is too high, the cost will be increased and it will be not conducive to centrifugal separation.

[0062] In some embodiments, in step (3), the etching treatment is performed at room temperature, such as 20°C, 21°C, 22°C, 23°C, 24°C, 25°C, etc., for 0.5-24h, such as 0.5h, 4h, 8h, 12h, 16h, 20h, 24h, etc. By controlling the temperature and time of the etching treatment, the hydrochloric acid and the nano-calcium carbonate can be completely reacted, the nano-calcium carbonate template is completely removed, and nitrogen self-doped mesoporous hollow nano-carbon spheres with better performance are obtained.

[0063] In some embodiments, in step (3), there is no particular limitation on the drying method, drying temperature and drying time, and the same may be referred to the drying method, drying temperature and drying time in step (1).

[0064] In some embodiments, in step (4), the phosphorus-containing compound includes at least one of sodium hypophosphite, ammonium hypophosphite and red phosphorus. The phosphorus source of the gas-solid reaction method is mainly sodium hypophosphite, ammonium hypophosphite and red phosphorus. When the heating temperature is increased to above 250°C, sodium hypophosphite will decompose to produce phosphine (PH3), and ammonium hypophosphite will also decompose to produce phosphine (PH3) but will also produce ammonia. For red phosphorus, phosphorus vapor will be produced when the heating temperature exceeds 400°C. Considering that sodium hypophosphite decomposes to produce a single gas phosphine (PH3), and the doping effect of phosphine (PH3) is better, sodium hypophosphite is preferably used.

[0065] In some embodiments, in step (4), the volume fraction of the sulfur-containing gas in the mixed atmosphere is 3-8%, for example, 3%, 4%, 5%, 6%, 7%, 8%, etc. When the volume fraction of the sulfur-containing gas is within the above range, it is beneficial to optimize the doping amount of the sulfur element. When the volume fraction of the sulfur-containing gas is too low, the doping amount of the sulfur element is too low, which is not conducive to exerting the synergistic effect of nitrogen, phosphorus and sulfur, that is, it is not conducive to changing the carbon layer spacing, increasing the surface functional groups and defects of the carbon material, providing more active sites, increasing the ion transfer rate, and enhancing the capacity effect. When the volume fraction of the sulfur-containing gas is too high, it is not conducive to recovering the sulfur-containing gas.

[0066] In some embodiments, in step (4), the sulfur-containing gas includes at least one of hydrogen sulfide, sulfur dioxide and sulfur trioxide. Both sulfur dioxide and sulfur trioxide are oxidizing and have an effect on other elements such as carbon, nitrogen and phosphorus, so hydrogen sulfide is preferred.

[0067] In some embodiments, in step (4), the second calcination treatment is calcined at 500-900°C, such as 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, etc., for 1-5h, such as 1h, 2h, 3h, 4h, 5h, etc. The second calcination treatment uses a phosphorus-containing compound to phosphate the nitrogen self-doped mesoporous hollow nano-carbon spheres, and uses a sulfur-containing gas to sulfidize the nitrogen self-doped mesoporous hollow nano-carbon spheres. The phosphating and sulfiding are carried out simultaneously to obtain nitrogen, phosphorus and sulfur self-doped mesoporous hollow nano-carbon spheres, that is, porous hollow carbon sphere composite materials. Within the above-mentioned calcination temperature and calcination time range, it is beneficial to obtain the target product with a phosphorus and sulfur doping amount within the specified content range, further optimize the synergistic effect of nitrogen, phosphorus and sulfur, and is beneficial to change the carbon layer spacing, increase the surface functional groups and defects of the carbon material, provide more active sites, increase the ion transfer rate, and improve the capacity.

[0068] In some embodiments, in step (4), the protective gas can refer to the protective gas in step (2).

[0069] In addition, an embodiment of the present invention further provides a sodium ion battery, the negative electrode active material of the sodium ion battery includes the porous hollow carbon sphere composite material of the embodiment of the present invention or the porous hollow carbon sphere composite material prepared by the preparation method of the embodiment of the present invention.

[0070] Due to the use of the porous hollow carbon sphere composite material of the embodiment of the present invention, or the porous hollow carbon sphere composite material prepared by the preparation method of the embodiment of the present invention, the sodium ion battery of the embodiment of the present invention has excellent discharge capacity, rate performance and cycle stability.

[0071] The present invention is described in detail below with reference to the embodiments and the accompanying drawings.

[0072] Example 1

[0073] A porous hollow carbon ball composite material, which is a mesoporous hollow nano-carbon ball co-doped with nitrogen, phosphorus and sulfur; the diameter of the mesoporous hollow nano-carbon ball is 70-100nm; the wall thickness of the mesoporous hollow nano-carbon ball is 10nm; the surface of the mesoporous hollow nano-carbon ball has mesopores with a pore size of 20-30nm; based on the total number of atoms in the porous hollow carbon ball composite material being 100%, the atomic percentage content of the nitrogen element is 8.56%; the atomic percentage content of the phosphorus element is 2.28%; and the atomic percentage content of the sulfur element is 2.94%.

[0074] The preparation method of the porous hollow carbon sphere composite material comprises the following steps:

[0075] (1) Preparation of polydopamine-coated nano-calcium carbonate (PDA@CaCO3):

[0076] 120 mg of tris (hydroxymethyl) aminomethane (Tris) (Aladdin, 99.8%) and 500 mg of nano calcium carbonate (Shanxi Xintai Hengxin Nanomaterial Co., Ltd., analytical grade) were ultrasonically dispersed in 100 mL of deionized water and stirred for 5 h to make the nano calcium carbonate evenly dispersed in the solution. 400 mg of dopamine hydrochloride (purity 99%, Aladdin) was added and stirred at room temperature for 36 h. The product was washed with deionized water and ethanol by centrifugation, and then dried in a vacuum tube at 60 ° C for 12 h to obtain the PDA@CaCO3 precursor.

[0077] (2) The first calcination treatment obtains nitrogen self-doped carbon-coated nano-calcium carbonate:

[0078] The PDA@CaCO3 precursor was calcined at 450 °C for 3 h (heating rate was 1 °C min-1) in an argon atmosphere. -1 ), and then calcined at 800 °C for 3 h (heating rate of 5 °C min -1 ) to obtain nitrogen self-doped carbon-coated nano-calcium carbonate.

[0079] (3) Etching treatment to obtain nitrogen self-doped mesoporous hollow nanocarbon spheres:

[0080] The calcined sample, i.e., nitrogen self-doped carbon-coated nano-calcium carbonate, was treated with 1 mol·L -1 The product was washed by centrifugation with deionized water and ethanol, and then dried in a vacuum tube at 60°C for 12 hours to obtain nitrogen self-doped mesoporous hollow nanocarbon spheres.

[0081] (4) Second calcination treatment for doping heteroatoms:

[0082] Weigh 1g of sodium hypophosphite and place it in a porcelain boat, and transfer the prepared nitrogen self-doped mesoporous hollow nanocarbon sphere powder to another porcelain boat. Put the two porcelain boats together in a tube furnace with a 5cm gap between them, and calcine them at 700℃ in a mixed atmosphere with a volume fraction ratio of 5%:95% of hydrogen sulfide and argon gas for 3h (heating rate of 5℃·min -1 ) for phosphating and sulfiding, and the copper sulfate solution absorbs the exhaust gas.

[0083] Application Example 1

[0084] Weigh 16 mg of the porous hollow carbon sphere composite material of Example 1 as the negative electrode active material, and 2 mg of Super P in a clean mortar, grind for 30 minutes, transfer to a weighing bottle, and vacuum dry for 0.5 hours. Add 40 mg of 5% PVDF solution (solvent is NMP), add appropriate amount of NMP to adjust the slurry to a suitable viscosity, and stir for 6 hours. Transfer the stirred negative electrode slurry to a flat copper foil, use a 100μm scraper, vacuum dry at 50°C for 12 hours to obtain a carbon negative electrode sheet; use 1.0 mol·L -1 NaClO4-EC / DMC; the sodium ion battery was assembled in an argon glove box, which consists of, from top to bottom, the negative electrode shell, nickel foam, sodium sheet, glass fiber separator, negative electrode sheet, and positive electrode shell.

[0085] Example 2

[0086] A porous hollow carbon ball composite material, the composite material is a mesoporous hollow nano-carbon ball co-doped with nitrogen, phosphorus and sulfur; the diameter of the mesoporous hollow nano-carbon ball is 70-100nm; the wall thickness of the mesoporous hollow nano-carbon ball is 10nm; the surface of the mesoporous hollow nano-carbon ball has mesopores with a pore size of 20-25nm; based on the total number of atoms in the porous hollow carbon ball composite material as 100%, the atomic percentage content of nitrogen is 8.06%; the atomic percentage content of phosphorus is 2.08%; and the atomic percentage content of sulfur is 2.34%.

[0087] The preparation method of the porous hollow carbon sphere composite material is the same as that of Example 1, except that dopamine hydrochloride is added in step (1) and then stirred at room temperature for 24 hours.

[0088] Application Example 2

[0089] The porous hollow carbon ball composite material of Example 2 is used as the negative electrode active material to assemble a sodium ion battery, and the assembly method is the same as that of Application Example 1.

[0090] Example 3

[0091] A porous hollow carbon ball composite material, the composite material is a mesoporous hollow nano-carbon ball co-doped with nitrogen, phosphorus and sulfur; the diameter of the mesoporous hollow nano-carbon ball is 70-100nm; the wall thickness of the mesoporous hollow nano-carbon ball is 10nm; the surface of the mesoporous hollow nano-carbon ball has mesopores with a pore size of 20-30nm; based on the total number of atoms in the porous hollow carbon ball composite material as 100%, the atomic percentage content of nitrogen is 7.56%; the atomic percentage content of phosphorus is 1.98%; and the atomic percentage content of sulfur is 2.04%.

[0092] The preparation method of this embodiment is the same as the preparation method of Example 1, except that in step (2), the PDA@CaCO3 precursor is calcined at 450°C for 12 h under an argon atmosphere.

[0093] Application Example 3

[0094] The porous hollow carbon ball composite material of Example 3 is used as the negative electrode active material to assemble a sodium ion battery, and the assembly method is the same as that of Application Example 1.

[0095] Example 4

[0096] A porous hollow carbon ball composite material, the composite material is a mesoporous hollow nano-carbon ball co-doped with nitrogen, phosphorus and sulfur; the diameter of the mesoporous hollow nano-carbon ball is 70-100nm; the wall thickness of the mesoporous hollow nano-carbon ball is 10nm; the surface of the mesoporous hollow nano-carbon ball has mesopores with a pore size of 20-30nm; based on the total number of atoms in the porous hollow carbon ball composite material as 100%, the atomic percentage content of nitrogen is 8.73%; the atomic percentage content of phosphorus is 2.45%; and the atomic percentage content of sulfur is 2.93%.

[0097] The preparation method of the porous hollow carbon sphere composite material is the same as that of Example 1, except that in step (4), calcination is performed in a mixed atmosphere of hydrogen sulfide and argon with a volume fraction ratio of 8%:92%.

[0098] Application Example 4

[0099] The porous hollow carbon ball composite material of Example 4 is used as the negative electrode active material to assemble a sodium ion battery, and the assembly method is the same as that of Application Example 1.

[0100] Example 5

[0101] A porous hollow carbon ball composite material, which is a mesoporous hollow nano-carbon ball co-doped with nitrogen, phosphorus and sulfur; the diameter of the mesoporous hollow nano-carbon ball is 70-100nm; the wall thickness of the mesoporous hollow nano-carbon ball is 10nm; the surface of the mesoporous hollow nano-carbon ball has mesopores with a pore size of 20-30nm; based on the total number of atoms in the porous hollow carbon ball composite material as 100%, the atomic percentage content of nitrogen is 8.93%; the atomic percentage content of phosphorus is 1.65%; and the atomic percentage content of sulfur is 3.23%.

[0102] The preparation method of the porous hollow carbon sphere composite material is the same as that of Example 1, except that the mass of the sodium hypophosphite in step (4) is 0.6 g.

[0103] Comparative Example 1

[0104] A solid nano carbon sphere.

[0105] The preparation method of the solid nano carbon sphere is as follows:

[0106] 120 mg of tris(hydroxymethyl)aminomethane (Tris) was ultrasonically dispersed in 100 mL of deionized water and stirred for 5 h. 400 mg of dopamine hydrochloride was added and stirred at room temperature for 36 h. The obtained product was centrifugally washed with deionized water and ethanol, and then dried in a vacuum tube at 60 ° C for 12 h. Calcinated at 450 ° C for 3 h (heating rate 1 ° C min-1) under argon atmosphere, and then calcined at 800 ° C for 3 h (heating rate 5 ° C min-1).

[0107] Application Comparative Example 1

[0108] The solid nano-carbon spheres of Comparative Example 1 were used as negative electrode active materials to assemble a sodium ion battery, and the assembling method was the same as that of Application Example 1.

[0109] Comparative Example 2

[0110] A porous hollow carbon ball composite material comprises mesoporous hollow nano-carbon balls and nitrogen elements co-doped in the mesoporous hollow nano-carbon balls; the diameter of the mesoporous hollow nano-carbon balls is 70-100nm; the wall thickness of the mesoporous hollow nano-carbon balls is 10m; the surface of the mesoporous hollow nano-carbon balls has mesopores with a pore size of 20-30nm; based on the total number of atoms of the porous hollow carbon ball composite material being 100%, the atomic percentage content of the nitrogen element is 8.56%.

[0111] The preparation method of the porous hollow carbon sphere composite material is the same as that of Example 1, except that step (4) is omitted.

[0112] Application Comparative Example 2

[0113] The porous hollow carbon ball composite material of Comparative Example 2 is used as the negative electrode active material to assemble a sodium ion battery, and the assembling method is the same as that of Application Example 1.

[0114] Comparative Example 3

[0115] A porous hollow carbon ball composite material, the composite material is a mesoporous hollow nano-carbon ball co-doped with nitrogen and phosphorus; the diameter of the mesoporous hollow nano-carbon ball is 70-100nm; the wall thickness of the mesoporous hollow nano-carbon ball is 10m; the surface of the mesoporous hollow nano-carbon ball has mesopores with a pore size of 20-30nm; based on the total number of atoms of the porous hollow carbon ball composite material as 100%, the atomic percentage content of the nitrogen element is 8.56%; the atomic percentage content of the phosphorus element is 2.28%.

[0116] The preparation method of the porous hollow carbon sphere composite material is the same as that of Example 1, except that in step (4), 1 g of sodium hypophosphite is weighed and placed in a porcelain boat, and the prepared nitrogen self-doped mesoporous hollow nanocarbon sphere powder is transferred to another porcelain boat. The two porcelain boats are placed in a tube furnace with a 5 cm interval between them, and calcined at 700°C in an argon atmosphere for 3 h (the heating rate is 5°C·min -1 ) for phosphating.

[0117] Application Comparative Example 3

[0118] The porous hollow carbon ball composite material of Comparative Example 3 is used as the negative electrode active material to assemble a sodium ion battery, and the assembling method is the same as that of Application Example 1.

[0119] Comparative Example 4

[0120] A porous hollow carbon ball composite material, the composite material is a nitrogen-doped mesoporous hollow nano-carbon ball; the diameter of the mesoporous hollow nano-carbon ball is 70-100nm; the wall thickness of the mesoporous hollow nano-carbon ball is 10nm; the surface of the mesoporous hollow nano-carbon ball has mesopores with a pore size of 20-30nm; based on the total number of atoms of the porous hollow carbon ball composite material being 100%, the atomic percentage content of the nitrogen element is 7.56%.

[0121] The preparation method of the porous hollow carbon sphere composite material is the same as the preparation method of Example 1, except that:

[0122] (2) Etching treatment to obtain polydopamine shell:

[0123] The PDA@CaCO3 precursor was heated to 1 mol·L -1 The product was etched with hydrochloric acid for 1 hour. The product was washed by centrifugation with deionized water and ethanol, and then dried in a vacuum tube at 60°C for 12 hours to obtain a polydopamine shell;

[0124] (3) The first calcination treatment obtains nitrogen self-doped mesoporous hollow nanocarbon spheres:

[0125] The polydopamine shell was calcined at 450 °C for 3 h (heating rate was 1 °C min-1) under argon atmosphere. -1 ), and then calcined at 800 °C for 3 h (heating rate of 5 °C min -1 ), to obtain nitrogen self-doped mesoporous hollow nanocarbon spheres;

[0126] And step (4) is omitted.

[0127] Application Comparative Example 4

[0128] The porous hollow carbon ball composite material of Comparative Example 4 is used as the negative electrode active material to assemble a sodium ion battery, and the assembling method is the same as that of Application Example 1.

[0129] Half-battery test: The equipment used for the constant current charge and discharge performance test is the Xinwei battery test system produced by Shenzhen Xinwei Electronics Co., Ltd., model CT-4000. After the battery is assembled, the charge and discharge performance test is carried out in a 30℃ constant temperature biochemical incubator. The pre-set cycle step or rate step is transferred, and the current density, charge and discharge voltage and other parameters are input to carry out the test. The current density is 0.5A·g -1 , the test voltage range is 0.01-3V. After the test, the charge and discharge performance of the electrode active material is judged by parameters such as charge and discharge specific capacity, cycle retention rate, and coulomb efficiency. The cyclic voltammetry test was performed using Shanghai Chenhua's CHI660 electrochemical workstation. Before the test, the open circuit voltage was measured using the electrochemical workstation, and the potential scan started from the open circuit voltage. When performing cyclic voltammetry tests on batteries that have not been charged or discharged, the direction of the scanning potential is consistent with the charge and discharge settings, and the scanning rate is 0.1mV·s -1 The electrochemical performance test results of the sodium ion batteries of Application Examples 1-5 and Comparative Examples 1-3 are as follows: Figure 1-2 And as shown in Table 1.

[0130] Table 1 Electrical performance test results of sodium ion batteries of Examples 1-5 and Comparative Examples 1-4

[0131] project Capacity retention after 50 cycles Coulomb efficiency after 50 cycles Application Example 1 77.19% 99.16% Application Example 2 75.28% 99.05% Application Example 3 71.15% 99.03% Application Example 4 74.58% 98.58% Application Example 5 70.76% 99.03% Application Comparative Example 1 46.60% 99.33% Application Comparative Example 2 52.05% 99.35% Application Example 3 50.28% 98.46% Application Comparative Example 4 50.69% 98.46%

[0132] Analysis of electrochemical performance test results:

[0133] Figure 1 It shows that the sodium ion battery at 0.5A·g -1 The charge-discharge curves of the first five cycles under the conditions of (a) and (b) are for the sodium ion battery of Example 1; (c) are for the sodium ion battery of Comparative Example 1; and (d) are for the sodium ion battery of Comparative Example 1. The sodium ion battery of Example 1 uses the nitrogen, phosphorus and sulfur co-doped mesoporous hollow nanocarbon sphere electrode of Example 1, and its initial discharge capacity and charge capacity are 3497 mAh·g -1 and 1121mAh·g -1 , corresponding to an initial efficiency of 32.1%; the sodium ion battery using comparative example 2 uses the nitrogen self-doped mesoporous hollow nanocarbon ball electrode of comparative example 2, and its initial discharge capacity and charging capacity are 1697mAh·g -1 and 374mAh·g -1 , corresponding to an initial efficiency of 22.0%. This result shows that phosphorus and sulfur addition can improve the material capacity and initial efficiency. The sodium ion battery using comparative example 1 uses the solid nanocarbon ball electrode of comparative example 1, and its initial discharge capacity and charging capacity are 102 mAh·g -1 and 47mAh·g -1, corresponding to a first efficiency of 46.1%. Compared with the material after the hollow nanostructure is formed, the capacity of the solid nanocarbon spheres is poor, indicating that the hollow nanostructure can provide space for the volume expansion of the particles after the cycle and improve the discharge capacity of the material.

[0134] The discharge performance of the sodium ion batteries of Application Example 1 and Application Comparative Examples 1 and 2 at different rates was characterized by rate cycle testing. Figure 2 It shows that its -1 The rate cyclability diagram under current density. The sodium ion battery of Example 1 is used at 0.8 A·g -1 , 1.5A·g -1 , 2A·g -1 , 4A g -1 , 5A g -1 , 6A·g -1 , 7A g -1 and 8A·g -1 At a current density of 3.14 W, the reversible specific capacity is 313 mAh g -1 、281mAh·g -1 、262mAh·g -1 , 242mAh·g -1 , 219mAh·g -1 , 202mAh·g -1 、179mAh·g -1 and 154mAh·g -1 When the current density is reduced to 0.8 A g -1 When the temperature is high, 297 mAh g -1 Reversible capacity. Compared with the sodium ion batteries of Comparative Examples 1 and 2, the sodium ion battery of Example 1 has a relatively high capacity at different current densities, indicating that nitrogen, phosphorus and sulfur co-doping can improve the material capacity and rate performance.

[0135] The structures of the nitrogen, phosphorus and sulfur co-doped mesoporous hollow nanocarbon spheres of Example 1, the nitrogen self-doped mesoporous hollow nanocarbon spheres of Comparative Example 2 and the solid nanocarbon spheres of Comparative Example 1 were characterized by XRD. All of them had a broad (002) diffraction peak, indicating that the materials of Example 1, Comparative Example 2 and Comparative Example 1 were all amorphous carbon. The interlayer spacing d of the carbon in the solid nanocarbon spheres of Comparative Example 1 was 002 The carbon interlayer spacing d of the nitrogen self-doped mesoporous hollow nanocarbon spheres in Comparative Example 2 is 0.359 nm. 002 The carbon interlayer spacing d of the nitrogen, phosphorus and sulfur co-doped mesoporous hollow nanocarbon spheres of Example 1 is 0.360 nm. 002 It is 0.373nm, indicating that nitrogen, phosphorus and sulfur co-doping can increase the interlayer spacing of carbon.

[0136] The structures of the nitrogen, phosphorus and sulfur co-doped mesoporous hollow nanocarbon spheres of Example 1, the nitrogen self-doped mesoporous hollow nanocarbon spheres of Comparative Example 2 and the solid nanocarbon spheres of Comparative Example 1 were characterized by Raman testing (using a laser with a wavelength of 633 nm). The results are as follows: Figure 3 shown. Figure 3 The three curves are all at 1300cm -1 and 1600cm -1 There are peaks, corresponding to the D band reflecting defects and disordered carbon and the G band reflecting reaction symmetry and crystallinity. D / I G The values ​​are 1.10, 1.12, and 1.19, respectively, indicating that the defects of the mesoporous hollow nanocarbon spheres in Example 1 increased after the nitrogen, phosphorus, and sulfur co-doping treatment. At the same time, compared with the solid nanocarbon spheres in Comparative Example 1 and the nitrogen self-doped mesoporous hollow nanocarbon spheres in Comparative Example 2, it is shown that nitrogen doping can also cause an increase in defects and increase active sites.

[0137] The morphologies of the nitrogen, phosphorus and sulfur co-doped mesoporous hollow nanocarbon spheres of Example 1, the nitrogen self-doped mesoporous hollow nanocarbon spheres of Comparative Example 2, and the solid nanocarbon spheres of Comparative Example 1 were characterized by SEM. Figure 4 As shown in the figure, the obtained mesoporous hollow nanocarbon spheres are many small spheres connected to each other, and the morphology of the material does not change after doping. By comparison, it can be seen that there are no mesopores on the surface of the solid nanocarbon spheres in Figures a and d, while there are mesopores on the surface of the mesoporous hollow nanocarbon spheres.

[0138] In addition, from the comparison between Application Example 1 and Application Example 2 in Table 1, it can be found that when the self-polymerization reaction time of dopamine hydrochloride in step (1) of Example 2 is relatively short, complete etching cannot be achieved, and the mesopore diameter is reduced, which is not conducive to the transmission of sodium ions, resulting in the cycle stability of the battery of Application Example 2 being not as good as that of Application Example 1.

[0139] From the comparison between Application Example 1 and Application Example 3 in Table 1, it can be seen that when the first calcination treatment in step (2) of Example 3 is only carried out at a relatively low temperature, even if the calcination time is extended, the heteroatom doping amount cannot be increased, resulting in the cycle performance of the battery of Application Example 3 being not as good as that of Application Example 1.

[0140] From the comparison between Application Example 1 and Application Example 4 in Table 1, it can be seen that when the amount of hydrogen sulfide used in step (4) of Example 4 is relatively high, the atomic percentage content of sulfur atoms cannot be increased, and the atomic percentage content of nitrogen elements will be reduced, resulting in the cycle performance of the battery of Application Example 4 being not as good as that of Application Example 1.

[0141] From the comparison between Application Example 1 and Application Example 5 in Table 1, it can be found that when the amount of sodium hypophosphite used in step (4) of Example 5 is relatively small, the atomic percentage content of phosphorus element is greatly reduced, resulting in the capacity retention rate of the battery of Application Example 5 being not as high as that of Application Example 1.

[0142] From the comparison between Example 2 and Example 4 in Table 1, it can be seen that when Example 4 swaps the order of the first calcination treatment and the etching treatment, the atomic percentage content of the nitrogen element decreases, causing the cycle performance of the battery of Example 4 to further deteriorate relative to that of Example 2.

[0143] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0144] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A porous hollow carbon sphere composite material, characterized in that: The composite material is mesoporous hollow nano carbon spheres co-doped with nitrogen, phosphorus and sulfur.

2. The porous hollow carbon sphere composite material according to claim 1, characterized in that: The diameter of the mesoporous hollow nano-carbon sphere is 70-100 nm; and / or the wall thickness of the mesoporous hollow nano-carbon sphere is 8-12 nm; and / or the surface of the mesoporous hollow nano-carbon sphere has mesopores with a pore size of 20-30 nm.

3. The porous hollow carbon sphere composite material according to claim 1 or 2, characterized in that: Taking the total atomic number of the porous hollow carbon ball composite material as 100%, the atomic percentage content of the nitrogen element is 7-9%; and / or the atomic percentage content of the phosphorus element is 1.5-3%; and / or the atomic percentage content of the sulfur element is 2-4%.

4. The method for preparing the porous hollow carbon sphere composite material according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) mixing dopamine hydrochloride, nano-calcium carbonate, a buffer and a solvent, separating and drying the reaction product after the reaction, and obtaining polydopamine-coated nano-calcium carbonate; (2) subjecting the polydopamine-coated nano-calcium carbonate to a first calcination treatment in a protective gas atmosphere to obtain nitrogen self-doped carbon-coated nano-calcium carbonate; (3) etching the nitrogen self-doped carbon-coated nano-calcium carbonate with an acidic etching solution, and then separating and drying the reaction product to obtain nitrogen self-doped mesoporous hollow nano-carbon spheres; (4) subjecting the nitrogen self-doped mesoporous hollow nano-carbon spheres and the phosphorus-containing compound to a second calcination treatment in a mixed atmosphere of a sulfur-containing gas and a protective gas to obtain the porous hollow carbon sphere composite material.

5. The method for preparing the porous hollow carbon sphere composite material according to claim 4, characterized in that: In step (1), the mass ratio of the dopamine hydrochloride to the nano-calcium carbonate is (3-5):5; and / or, the reaction is carried out at room temperature under stirring for 24-48 hours.

6. The method for preparing the porous hollow carbon sphere composite material according to claim 4, characterized in that: In step (2), the first calcination treatment is calcination at 400-900°C for 4-12h; preferably, the first calcination treatment is calcination at 400-500°C for 2-5h and then calcination at 700-900°C for 2-5h.

7. The method for preparing the porous hollow carbon sphere composite material according to claim 4, characterized in that: In step (3), the acidic etching solution is selected from at least one of hydrochloric acid, acetic acid, sulfuric acid, nitric acid and phosphoric acid; preferably, the concentration of the acidic etching solution is 0.2-1.5 mol·L -1 .

8. The method for preparing the porous hollow carbon sphere composite material according to claim 4, characterized in that: In step (4), the phosphorus-containing compound includes at least one of sodium hypophosphite, ammonium hypophosphite and red phosphorus; and / or the sulfur-containing gas includes at least one of hydrogen sulfide, sulfur dioxide and sulfur trioxide.

9. The method for preparing the porous hollow carbon sphere composite material according to claim 4, characterized in that: In step (4), the second calcination treatment is calcined at 500-900° C. for 1-5 hours.

10. A sodium ion battery, characterized in that: The negative electrode active material of the sodium ion battery comprises the porous hollow carbon sphere composite material according to any one of claims 1 to 3 or the porous hollow carbon sphere composite material prepared by the preparation method according to any one of claims 4 to 9.

Citation Information

Patent Citations

  • Novel macro- and micro-porous thin film carbon material and preparation method of same

    CN106564873A

  • Nitrogen-doped hollow carbon sphere composite and preparation method and application thereof

    CN108417803A

  • Preparation method of nitrogen-enriched material of porous carbon nanosheet-filled hollow carbon sphere

    CN108923026A

  • Preparation method and application of doped carbon / silicon composite material

    CN110176592A

  • Nitrogen-doped hollow carbon sphere taking phthalocyanine as precursor as well as preparation method and application thereof

    CN110676443A